Perkembangan perkebunan swasta di Subang, Jawa Barat: P&T Lands Tahun 1812-1957 - Kharimah, Ghina (Universitas Negeri Malang, 2023)
Pamanoekan en Tjiasemlanden, or P and T Lands, is a privately held plantation corporation that was established in 1813. This article describes the development of P and T Lands from 1812 to 1957, from the establishment of the P and T Lands firm, how this plantation company worked, and how the plantation company experienced a decrease. This study uses historical research methods consisting of topic selection, heuristics, verification, interpretation, and historiography. This study found that after being purchased by British businessmen, the estates of Pamanukan and Ciasem were re-managed. During Hofland's tenure, P and T Lands, on the other hand, really gained up. Various infrastructures were constructed, and the plantation's outcomes provided the proprietors with numerous advantages. Since Peter William Hofland's death, P and T Lands has been in decline, and the company was eventually seized and passed to the Indonesian government. P dan T Lands atau Pamanoekan en Tjiasemlanden merupakan sebuah perusahaan perkebunan milik swasta yang berdiri sejak tahun 1813. Artikel ini menjelaskan perkembangan P dan T Lands dari tahun 1812 sampai 1957, mulai dari awal berdirinya perusahaan P dan T Lands, bagaimana perusahaan perkebunan ini beroperasi, dan bagaimana perusahaan perkebunan ini mengalami kemunduran. Penelitian ini menggunakan metode penelitian sejarah yang terdiri dari pemilihan topik, heuristik, verifikasi, interpretasi, dan historiografi. Penelitian ini menemukan bahwa tanah Pamanukan dan Ciasem mulai kembali dikelola setelah dibeli oleh pengusaha Inggris. Namun, P dan T Lands sendiri benar-benar berkembang pada masa kepemilikan Hofland. Berbagai infrastruktur dibangun dan hasil dari perkebunan yang memberikan banyak keuntungan bagi para pemilik. P dan T Lands mulai mengalami kemunduran sejak Peter William Hofland meninggal yang kemudian nantinya dinasionalisasi dan menjadi milik Pemerintah Indonesia